ANALISIS DROP CALL PADA BTS (BASE TRANCEIVER STATION) NOKIA ULTRASITE EDGE SITE KAMPUNG NAGA DI PT.INDOSAT Tbk Branch Tasikmalaya - , PRATIWI SEFTIANINGTYAS; , Ir. Sri Lestari., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Final project report titled \\"ANALYSIS CALL DROP ON BTS NOKIA ULRASITE EDGE SITE KAMPUNG NAGA\\". In this final project report writing research method used is through literature, field observations and method of question and answer with the employee or the supervisor of field work to obtain the necessary data. The author makes the site Kampung Naga as material analysis to final project report because the authors work directly in Ultrasite EDGE Nokia BTS installation and analyze problems to alarm 7725 (Traffic Channel Acivation Failure) and 7745 (Channel Failure Rate Defined Above Threshold) causing call drop on site Kampung Naga. Alarm causes the decline in some performasi network, including traffic channel parameters, TCH Success Rate, and dropcall percentage reached 85%. Therefore, the authors perform troubleshooting in a way which is mounted on a timeslot synchronization with the BTS configuration contained in the BSC as a solution to this dropcall.